2007
DOI: 10.1016/j.amjhyper.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Casein Hydrolysate (C12 Peptide) Reduces Blood Pressure in Prehypertensive Subjects

Abstract: This study shows that C12 Peptide reduces BP in prehypertensive people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Moreover, Sekyia et al (38) and Sugai (39) did not use control groups. Double-blinding was reported only by Cadée et al (42) and Townsend et al (41) . Taken together, the five trials appear to have a high risk of bias, which weakens the strength of evidence supporting their conclusions.…”
Section: Impact Of Milk Consumption On Cardiovascular Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Sekyia et al (38) and Sugai (39) did not use control groups. Double-blinding was reported only by Cadée et al (42) and Townsend et al (41) . Taken together, the five trials appear to have a high risk of bias, which weakens the strength of evidence supporting their conclusions.…”
Section: Impact Of Milk Consumption On Cardiovascular Healthmentioning
confidence: 99%
“…Townsend et al (41) performed an acute, randomised, single-blind, cross-over pilot study in ten hypertensive participants who were assigned randomly to one of the five treatment regimens (100 mg C12; 200 mg C12; 50 mg C12 þ 877 mg alginic acid; 100 mg C12 þ 1754 mg alginic acid; placebo). Significant reductions in BP were only seen in the group consuming the high dose of C12 (100 mg) combined with alginic acid (1754 mg): 2 9·2 mmHg in SBP 6 h after oral administration compared with 2 h after (42) 48 , ingestion (P¼0·02), and 26·0 mmHg in DBP 6 h after oral administration compared with 2 h (P¼0·015). Cadée et al (42) studied the effects of a daily intake of 3·8 g C12 peptide in forty-eight Taiwanese subjects.…”
Section: Impact Of Milk Consumption On Cardiovascular Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these peptides, the two lactotripeptides VPP and IPP have been the subject of various in vivo studies using fermented-milk products [13]. Additionally, a potent ACE-inhibiting effect was obtained in both hypertensive and prehypertensive humans in a double-blind, placebo-controlled trial with a bovine casein hydrolysate [17,127]. The effect was attributed to a longer peptide representing the sequence f23-34 of α s1 -casein [25], but it remains questionable whether such peptides can be absorbed in an intact form.…”
Section: Orally Active Ace-inhibitory Peptidesmentioning
confidence: 99%
“…For example, Ballard et al (16) used 5 g of a whey protein hydrolysate per d to observe a vascular endothelial response. In addition, Cadee et al (17) used 3·8 g of a bovine casein hydrolysate per d and observed a decrease of respectively -10·7 and -6·9 mmHg in SBP and DBP compared with the baseline after a 4-week intervention period. In fact, the Food and Drug Administration has approved a claim for this protein hydrolysate, which has been called C12 Peption® and for which the targeted daily intake has been set at 4·2 g/d.…”
Section: Discussionmentioning
confidence: 99%